Maintenance of vascular integrity by pericytes is essential for normal kidney function - Lemos, Dario R. (Am J Physiol Renal Physiol, 2016)
Pericytes are tissue-resident mesenchymal progenitor cells anatomically associated with the vasculature that have been shown to participate in tissue regeneration. Here, we tested the hypothesis that kidney pericytes, derived from FoxD1(+) mesodermal progenitors during embryogenesis, are necessary for postnatal kidney homeostasis. Diphtheria toxin delivery to FoxD1Cre::RsDTR transgenic mice resulted in selective ablation of >90% of kidney pericytes but not other cell lineages. Abrupt increases in plasma creatinine, blood urea nitrogen, and albuminuria within 96 h indicated acute kidney injury in pericyte-ablated mice. Loss of pericytes led to a rapid accumulation of neutral lipid vacuoles, swollen mitochondria, and apoptosis in tubular epithelial cells. Pericyte ablation led to endothelial cell swelling, reduced expression of vascular homeostasis markers, and peritubular capillary loss. Despite the observed injury, no signs of the acute inflammatory response were observed. Pathway enrichment analysis of genes expressed in kidney pericytes in vivo identified basement membrane proteins, angiogenic factors, and factors regulating vascular tone as major regulators of vascular function. Using novel microphysiological devices, we recapitulated human kidney peritubular capillaries coated with pericytes and showed that pericytes regulate permeability, basement membrane deposition, and microvascular tone. These findings suggest that through the active support of the microvasculature, pericytes are essential to adult kidney homeostasis.